2015
DOI: 10.3758/s13414-015-1033-z
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive understanding of the relationship between the elasticity of objects and kinematic patterns of collisions

Abstract: Horizontal collisions have long been used as a tool for exploring people's intuitive understanding of elementary physical laws. Here, we explored intuitive understanding of the relationship between the kinematic patterns of collisions and the elasticity of the colliding objects. In Experiment 1A, we manipulated the simulated materials of two virtually colliding spheres and asked the participants to judge whether the simulated collisions appeared Bnatural^or Bunnatural.^We did the same in Experiments 1B and 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…For example, Hast and Howe (2015) found that while almost 90% of elementary students incorrectly predicted that heavier objects would fall faster than lighter objects, over three-quarters of the students indicated that animations where the heavy and light objects fall at the same rate were correct. Similar results favoring recognition tasks where participants select animations that align with a canonical conceptual understanding, and reject animations that align with their non-canonical conceptual understanding expressed on explicit tasks have been found for projectile motion (Cooke and Breedin, 1994; Hecht and Bertamini, 2000), two-dimensional motion (Hast and Howe, 2017), circular motion (Kaiser et al , 1985a, 1992), gravitational free fall (Hast and Howe, 2015; Howe et al , 2012) and conservation of momentum (Kaiser and Proffitt, 1984, 1987; Howe et al , 2014; Vicovaro and Burigana, 2016), even when the incorrect motion endorsed by participants on the explicit tasks are included in the recognition tasks.…”
Section: Impact Of Stimulus and Task Characteristics On Measuring Understanding Of The Physical Worldsupporting
confidence: 63%
See 1 more Smart Citation
“…For example, Hast and Howe (2015) found that while almost 90% of elementary students incorrectly predicted that heavier objects would fall faster than lighter objects, over three-quarters of the students indicated that animations where the heavy and light objects fall at the same rate were correct. Similar results favoring recognition tasks where participants select animations that align with a canonical conceptual understanding, and reject animations that align with their non-canonical conceptual understanding expressed on explicit tasks have been found for projectile motion (Cooke and Breedin, 1994; Hecht and Bertamini, 2000), two-dimensional motion (Hast and Howe, 2017), circular motion (Kaiser et al , 1985a, 1992), gravitational free fall (Hast and Howe, 2015; Howe et al , 2012) and conservation of momentum (Kaiser and Proffitt, 1984, 1987; Howe et al , 2014; Vicovaro and Burigana, 2016), even when the incorrect motion endorsed by participants on the explicit tasks are included in the recognition tasks.…”
Section: Impact Of Stimulus and Task Characteristics On Measuring Understanding Of The Physical Worldsupporting
confidence: 63%
“…Such tasks often result in low student accuracy. In contrast, participant accuracy is routinely superior for recognition tasks that ask participants to observe correct and incorrect animations of physical scenarios, and then to select the animation that correctly represents motion in the scenario (Hecht and Bertamini, 2000; Vicovaro and Burigana, 2016). For example, Hast and Howe (2015) found that while almost 90% of elementary students incorrectly predicted that heavier objects would fall faster than lighter objects, over three-quarters of the students indicated that animations where the heavy and light objects fall at the same rate were correct.…”
Section: Impact Of Stimulus and Task Characteristics On Measuring Understanding Of The Physical Worldmentioning
confidence: 99%
“…In the light of these results, we believe that speed overestimation effect could be added to the list of functional effects of causality on the low-level properties of the scene such as spatial binding ( Buehner & Humphreys, 2010 ), avoiding overlapping ( Scholl & Nakayama, 2004 ), and speed perception in the naive physics of collisions and impetus theories ( Hubbard, 2013a , 2013b ; Parovel & Casco, 2006 ; Vicovaro, 2012 , 2018 ; Vicovaro et al., 2020 ; Vicovaro & Burigana, 2014 , 2016 ; White, 2009 ), supporting the hypothesis that social causality and animacy perception are deeply rooted in early visual processing ( Scholl & Gao, 2013 ), being largely automatic and resistant to higher level beliefs and intentions.…”
Section: Discussionmentioning
confidence: 96%
“…In launching events, moreover, there can also be a systematic error in remembering the vanishing position of the second moving object during its postcollision motion ( De Sá Teixeira et al., 2008 ; Hubbard et al., 2001 ; Hubbard & Ruppel, 2002 ). About speed, if Michotte (1946/1963 ) demonstrated the crucial role of objective speed ratio between A and B in perception of causality (see also Schlottmann & Anderson, 1993 ), apparent kinematics itself seems to be biased in causal events: Several works suggested that the perceived speed of B can be influenced by the speed of A, coherently to the naive physics of collisions and impetus theories ( De Sá Teixeira et al., 2008 ; Hubbard, 2013a , 2013b ; Parovel & Casco, 2006 ; see also Vicovaro, 2012 , 2018 ; Vicovaro et al., 2020 ; Vicovaro & Burigana, 2014 , 2016 ) and to White’s (2009) property transmission hypothesis. Parovel and Casco (2006) showed that the speed of the second object in causal events was overestimated for a wide range of speeds of the first object (launcher) but accurately assessed in noncausal events.…”
mentioning
confidence: 98%
“…To make an illustrative example, since Michotte’s (1946/1963) seminal study on the perception of causality, the intuitive physics of collisions has been mainly studied using simple animations involving immaterial shapes moving in one or two dimensions (e.g., Gerstenberg et al, 2012; Lau & Brady, 2020; Runeson & Vedeler, 1993; Sanborn et al, 2013; Smith & Vul, 2013; Vicovaro et al, 2020; White, 2007). Only few studies have attempted to increase the realism of simulated collisions, for instance by using 3D spheres made of definite simulated materials (Vicovaro, 2018; Vicovaro & Burigana, 2016) or by mimicking the effects of friction and rotation on the collision behavior of the stimuli (Meding et al, 2020; Reitsma & O’Sullivan, 2009). The results of these studies suggest that the realism of the stimuli has a substantial influence on subjective judgments of the naturalness of collisions.…”
Section: The Heuristic Perspectivementioning
confidence: 99%